ADSORPTION OF ALKYLTRIMETHYL AMMONIUM BROMIDE AT THE AIR-WATER-INTERFACE - Lu, J; Simister, E; Thomas, R; Penfold, J (Publ by Springer-Verlag GmbH and Company KG, 1993)
The composition and structure of soluble monolayers of cationic surfactants of alkyltrimethyl ammonium bromide adsorbed at the air/water interface have been studied by the neutron reflection technique. - At the critical micelle concentration (CMC) the area per surfactant molecule was found to 55±3 A2 for decyl trimethyl ammonium bromide (C10TAB), 48±3 A2 for tetradecyl trimethyl ammonium bromide (C14TAB), and 43±3 A2 for octadecyl trimethyl ammonium bromide (C18TAB). - The determination of the structure of the surfactant layers at their corresponding CMC was based on three different isotopic combinations of water and surfactant. The results were analysed using both optical matrix method and the kinematic approach. The thickness of the whole surfactant monolayer was found to be 19±2 A for C10TAB, 22±2 A for C14TAB and C18TAB. The thickness of alkyl chain layer out of water was found to be 11±1 A for C10TAB and 12.5±1 A for the two other surfactants. The amount of alkyl chain immersed in water was found to be 30-40%, with shorter chain surfactants being more immersed.